Article in Search of an Author: Exciting Collaboration or Unethical Conduct? - Marin Gillis; Judy Hanrahan (Association of American Medical Colleges, 2010)
Abstract At the University of Nevada School of Medicine we employ a problem-based learning (PBL) methodology using progressive disclosure cases to teach clinical problem-solving. While this method is used heavily in one first-year course entitled Clinical Problem Solving, we are working towards employing this modality across the entire curriculum. The progressive disclosure cases used at our school primarily contain clinical science problems. In an effort to expand the modality of progressive disclosure cases to the ethics and professionalism curriculum, we created this module. The case focuses on medical professionalism and introduces students to an ethically problematic scenario in academic medicine. This assignment was given to first-year medical students prior to the summer break where most students participate in clinical and basic science research. This is an interesting and practical way to learn about one's professional duties and other governing policies.